1990
DOI: 10.1192/bjp.156.2.204
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic Performance in Schizophrenia: a Comparison of Acute and Chronic Patients

Abstract: A computer-assisted analysis of samples of free speech from acute schizophrenics (n = 50), chronic schizophrenics (n = 27) and normal subjects (n = 50) enabled a comparison of the linguistic profiles of the three groups. The chronic group consistently emerged as the most impaired, on measures of complexity, integrity (error) and fluency of speech, with the acute patients performing less well than normal speakers but better than chronic patients. Demographic differences could account for only a small number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1
5

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(45 citation statements)
references
References 0 publications
3
36
1
5
Order By: Relevance
“…It could result from an overall cognitive deficit, difficulty concentrating, distraction, or a preference for expressing simpler ideas. Thomas et al (1987Thomas et al ( , 1990 found greater syntactic simplification in patients with negative symptoms than in those with positive symptoms. The same research group further found that syntactic complexity diminishes as the chronic patient's condition deteriorates , King et al (1990)).…”
Section: Simplificationmentioning
confidence: 96%
“…It could result from an overall cognitive deficit, difficulty concentrating, distraction, or a preference for expressing simpler ideas. Thomas et al (1987Thomas et al ( , 1990 found greater syntactic simplification in patients with negative symptoms than in those with positive symptoms. The same research group further found that syntactic complexity diminishes as the chronic patient's condition deteriorates , King et al (1990)).…”
Section: Simplificationmentioning
confidence: 96%
“…As far as language disturbances in SZ are concerned, it is known that patients with this disease generally have difficulty processing semantic aspects of language (Anand, Wales, Jackson, & Copolov, 1994;Blaney, 1974;Nestor et al, 2001;Paulsen et al, 1996), combining semantic and syntactic information (Condray, Steinhauer, Cohen, van Kammen, & Kasparek, 1999;Condray, Steinhauer, van Kammen, & Kasparek, 2002;Sitnikova, Salisbury, Kuperberg, & Holcomb, 2002;Thomas, King, Fraser, & Kendell, 1990), creating lexico-semantic associations (Salisbury, O'Donnell, McCarley, Nestor, & Shenton, 2000;Salisbury, Shenton, Nestor, & McCarley, 2002;Sitnikova et al, 2002;Titone, Levy, & Holzman, 2000), and accessing and using lexical knowledge (McKenna & Oh, 2005). They also exhibit deficits in verbal fluency, especially in category fluency (Bokat & Goldberg, 2003;Kremen, Seidman, Faraone, & Tsuang, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the author came to the conclusion that speech output lacking cohesion may have been caused by different pathophysiologic processes for patients with and without negative symptoms, and that these differences may be decisive for patients to become either treatment responders or nonresponders. As to the time course of language disturbances, Thomas et al [25], in a study of chronic schizophrenia in the community and in long-term wards, found that poor linguistic performance was related to the illness process, and not to institutionalization. Similarly, King et al [26], in their 3-year follow-up of patients, observed a deterioration of language, and particularly syntax, in the schizophrenic process.…”
Section: Introductionmentioning
confidence: 99%